PEMBERDAYAAN KESENIAN KETHOPRAK SEBAGAI MEDIA SOSIALISASI PROGRAM PEMERINTAH BAGI MASYARAKAT PEDESAAN DI DESA NGEMPLAK KECAMATAN KANDANGAN KABUPATEN TEMANGGUNG - Nur Salim (Abdi Seni, 2020)
Ngemplak Village, Kandangan Subdistrict, Temanggung Regency has a variety of artistic and cultural potential. This dedication activity is focused on one of the arts owned by Desa Ngemplak, namely ketoprak. Ketoprak art was chosen based on the urgency level of the problem related to the context of the community. Based on various problems faced by partners, the author prioritizes these issues into three points including: (1) The lack or absence of activity in the Kethoprak art group in Ngemplak Village; (2) There is no form of development of the art of kethoprak as a medium of socialization; (3) Public awareness of government programs is still low. Based on the problems faced, the author uses several concepts as a solution tool. These concepts include the concepts of empowerment, art concepts, and media socialization. The concept building is used as the basis for determining the method used to achieve the goal. The main method used in this activity is the method of community participation. The stages are in the form of preparation, implementation and evaluation stages of programs or activities. The results achieved in the Thematic Community Service Activities Program including Articles are the Ketoprak art of the Wahyu Manunggal group that has experienced a vacuum for 13 years and can be empowered again. Furthermore, the results of this activity are in the form of art development, in terms of their functions. Kethoprak which was originally an entertainment media was then used as a medium to socialize the Ngemplak Village programs.Keywords: Empowerment, Ketoprak, Socialization Media.